PI+PD type fuzzy logic controlled dual-arm robot in load transfer - Hacioglu, Yuksel (Strojniški vestnik, 2008)
This paper presents a PI+PD type fuzzy logic control method for simultaneous cooperative motion of a dual arm robot in load transfer tasks. First, physical model of dual arm robot with the load are presented and dynamic equations of the system are derived while constrained conditions are also taken into account. Since fuzzy logic controllers can successfully be designed even if the exact mathematical model of the system is unknown, this control method is preferred in many applications. Therefore, PI+PD type fuzzy logic controller is introduced to achieve cooperative coordination of dual arms. In order to verify the safety performance of the proposed controller, unexpected disturbances are introduced to the system. These are noise components, which are thought as disturbance torques, and an elastic element unintentionally catching the first robot arm. Finally, numerical results are presented and the performance of the control method is discussed.
Keywords: mehka logika; roboti; gibanje